1999
DOI: 10.1038/sj.bjc.6690764
|View full text |Cite
|
Sign up to set email alerts
|

The equilibrium and kinetic drug binding properties of the mouse P-gp1a and P-gp1b P-glycoproteins are similar

Abstract: SummaryThe gene encoding the multidrug resistance P-glycoprotein (P-gp) is duplicated in rodent species and the functional basis for this remains unresolved. Despite a high sequence similarity, the mouse P-gp1a and P-gp1b isoforms show distinct patterns of tissue distribution which suggest a specific role of the P-gp1b isoform in steroid transport. In the present study possible biochemical differences between the isoforms were directly investigated at the level of drug interaction. There was no detectable diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…[40][41][42][43] However, these earlier studies used indirect tests to assess substrate specificity and their significance has been questioned by more recent studies, which have reported no difference in the affinity of the 2 isoforms toward vinblastine. 38 It was concluded in these more recent studies that if any difference in transport exists between the 2 P-gp isoforms, it must occur at a step subsequent to binding, such as the translocation step or linkage between drug binding and ATP hydrolysis. 38 It is possible that sertraline can differentially affect the expression of Abcb1a and Abcb1b in the placenta and BBB.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42][43] However, these earlier studies used indirect tests to assess substrate specificity and their significance has been questioned by more recent studies, which have reported no difference in the affinity of the 2 isoforms toward vinblastine. 38 It was concluded in these more recent studies that if any difference in transport exists between the 2 P-gp isoforms, it must occur at a step subsequent to binding, such as the translocation step or linkage between drug binding and ATP hydrolysis. 38 It is possible that sertraline can differentially affect the expression of Abcb1a and Abcb1b in the placenta and BBB.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their high sequence similarity (80% at amino acid level), the observation that functional dierences exist is not unexpected. It has been shown that the two murine drug transporting isoforms, Mdr1a and Mdr1b, display overlapping, but distinct drug resistance phenotypes (Tang-Wai et al, 1995), and transport [ 3 H]vinblastine with dierent eciencies (Yang et al, 1990), in spite of their equal anity and binding capacity towards this substrate (Taylor et al, 1999). Moreover, as summarized by Ambudkar et al (1999), studies with mutated Pgps revealed that a change of only one amino acid may already dramatically aect the initial rate of drug uptake in accumulation assays with transfected cells.…”
Section: Discussionmentioning
confidence: 99%
“…mdr3 is referred to as the most effective isoform in detoxification, and mdr1 as the isoform preferably associated with the transport of steroid hormones (Yang et al, 1989;Gottesman and Pastan, 1993). Interestingly, Taylor et al (1999) found no significant differences between the mdr3 and mdr1 isoforms in the nature of drug-binding sites and suggested that the presence of multiple isoforms of Pgp alMdr expression in estrous cycle 759 Mice which are homozygous for a disruption of mdr1 or mdr3 are apparently healthy (Borst et al, 1993). In 1997, Schinkel et al obtained mice which, although homozygously deficient for the mdr1 and mdr3 genes combined, were healthy and fertile.…”
Section: Discussionmentioning
confidence: 99%